PERAN GURU BK DALAM MEMBANGUN KEBERMAKNAAN BELAJAR SISWA - Rika Ayuni; Mega Natasya; Gusman Lesmana (Nirta Learning Centre, 2026)
Meaningful learning is a fundamental element in the educational process that influences students' motivation, achievement, and psychological well-being. This study aims to analyze the role of Guidance and Counseling (BK) teachers in fostering meaningful learning in students in the contemporary education era. Using a qualitative literature review, this study examines various scientific sources from 2017 to 2025 that discuss the role of guidance and counseling teachers, meaningful learning, and strategies for developing meaning in educational contexts. The results indicate that guidance and counseling teachers play a strategic role in building meaningful learning for students through four main dimensions: responsive services to students' psychological needs, developing self-determination and learning autonomy, facilitating the exploration of values ​​and life goals, and collaborating with educational stakeholders. Guidance and counseling teachers act as facilitators, counselors, advocates, and collaborators in helping students find personal meaning in their learning process. Implementing comprehensive and planned guidance and counseling services can increase student engagement, reduce academic anxiety, and encourage deeper learning. This study recommends improving guidance and counseling teachers' competencies in a meaning-centered counseling approach, integrating technology into guidance and counseling services, and strengthening multi-stakeholder collaboration within the education ecosystem.